Kontribusi Science dalam Pembelajaran PAI - Vialinda Siswati (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2016)
The prominent role of science towards the learning of Islamic religious education is, the result of mutual dialogue between science and religious education of Islam is expected to strengthen the relationship of both because it is both the science is a unity that always has a goal and vision to reach piety Allah SWT both in world life and hereafter. In its application, it is time we do Islamization of science, because the issue of Islamization of science is not new.The purpose of writing this article is to provide descriptions of the definition of science and its relationship in Islamic religious education and analyze the role of science in learning Islamic religious education.